Performance evaluation of turkish mutual funds: market timing and persistence analysis - Abbasov, Elnur (My University, 2010)
Degree Awarded and Date: Master of Science - 2010 ABSTRACT As active participants of the capital market, mutual funds gained great attention of academic researchers in the field of finance since 1960’s. With the drastic growth of mutual funds, increasing emphasis has been placed on the question of proper performance evaluation. Although there are a number of academic studies devoted to measuring performance of Turkish mutual funds, few of them focused on the issue of assessment of fund managers’ market timing ability that is successfully forecasting the market movements, and analysis of persistence in performance of Turkish mutual funds. Our research aims to analyze timing ability of Turkish fund managers and to investigate whether persistence phenomenon exists in the Turkish mutual fund universe for the short-term period. In order to explore whether mutual fund managers were successful in forecasting the market movement and how much did the timing ability have impact on earning higher returns, we employed Treynor and Mazuy’s model with the quadratic variable and Henriksson and Merton’s model with the dummy variable. Testing of performance persistence in the short-run was implemented through application of Carhart’s 4-factor model, since it was assumed to capture market anomalies like size, ME/ BE ratio and short-term past return. The results imply that market prediction skill of Turkish mutual fund managers played an important role in earning abnormal returns and staying in the top rank. However, failure of momentum factor to explain the fund excess returns suggested that Turkish mutual funds did not exhibit performance persistence in the short-run.……………………………. KEY WORDS: Mutual funds, Performance evaluation, Market timing, Performance persistence
Keywords: Muhasebe; Performans Değerleme; Sermaye Piyasası; Yatırım Fonu